Stimulation of erythroblast maturation in vitro by sphingolipids - R.B. Clayton; J.M. Cooper; Tore Curstedt; Jan Sjövall; Henry Borsook; J. Chin; A. Schwarz (Journal of Lipid Research, 1974)
A lipid factor previously isolated from leukocytes and found to stimulate basophilic erythroblast formation in an in vitro system of incubated rabbit bone marrow cells has been analyzed by thin-layer chromatography, gas–liquid chromatography, and gas–liquid chromatography–mass spectrometry. The biologically active components are sphingosine ceramides of tetracosanoic and dehydrotetracosanoic acids. Tests of a series of related ceramides show a high degree of structural specificity for the C24-N-acyl compounds with significant but markedly lower activity of the C22 analog. Commercially available sphingomyelin shows activity comparable to that of the tetracosanoic acid ceramide. Sphingosine and tetracosanic acid supplied in equimolar amounts have negligible activity. The results, in the context of other findings, suggest a possible supportive role of plasma ceramides and sphingomyelins in red cell maturation.